2012
DOI: 10.1039/c2cc34267g
|View full text |Cite
|
Sign up to set email alerts
|

Live cell imaging of lysosomal pH changes with pH responsive ratiometric lanthanide probes

Abstract: Europium and terbium complexes of two structurally related ligands have been evaluated as optical probes to monitor changes in lysosomal pH; calibration using ionophores and fluorescent probes allows monitoring of the time dependence of lysosomal pH change, examining the green/red intensity ratio from internalised Tb-Eu complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
83
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 31 publications
2
83
0
Order By: Relevance
“…Much of the current research in the area of lanthanide complexation chemistry is focussed on the development of emissive europium complexes as ratiometric probes for biological analytes. 31,131,160,161 The sensitivity of the europium emission spectral form to the metal coordination environment is key to these advances and terbium is often overlooked. This example illustrates nicely how the use of CPL spectroscopy may be able to facilitate the use of terbium complexes as emissive probes, where changes in g em at a given wavelength could be used to indicate the presence of a given analyte.…”
Section: Studies Using Circular Dichroismmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the current research in the area of lanthanide complexation chemistry is focussed on the development of emissive europium complexes as ratiometric probes for biological analytes. 31,131,160,161 The sensitivity of the europium emission spectral form to the metal coordination environment is key to these advances and terbium is often overlooked. This example illustrates nicely how the use of CPL spectroscopy may be able to facilitate the use of terbium complexes as emissive probes, where changes in g em at a given wavelength could be used to indicate the presence of a given analyte.…”
Section: Studies Using Circular Dichroismmentioning
confidence: 99%
“…Changes in the to an altered CPL output. 131 In this system, a sulphonamide moiety is incorporated into the ligand framework, which is deprotonated at high pH and able to bind to the lanthanide centre. However, at low pH this is not the case and the coordination sphere is instead completed by a bound water molecule.…”
mentioning
confidence: 99%
“…Time-resolved confocal microscopy has also been explored (19,20). Numerous studies have reported both time-gated and steady-state imaging of responsive lanthanide sensors in living cells, including sensors for Zn 2þ , bicarbonate, pH, and singlet oxygen (21)(22)(23)(24). Lanthanide biosensors may be designed as responsive probes that exhibit an analyte-dependent change in emission intensity or lifetime (6), or as FRET-based systems that use Tb(III) or Eu(III) complexes as donors and FPs, organic dyes, or even quantum dots as acceptors (8,25).…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction of lysosomal structure or function is associated with multiple pathologies, including inflammation, cancer, neurodegenerative disease, and specific lysosomal storage diseases such as Tay-Sachs12345678910111213141516. Currently, there are limited numbers of fluorescent probes that efficiently enable a comprehensive evaluation of the structure/function correlates of lysosomes17181920212223242526272829303132. Cellular compartments with a low internal pH (pH 4.0-6.0), including the lysosome, enable basic amines of low ionic strength to selectively target and thereby explore the synthesis and actions of lysosomes.…”
mentioning
confidence: 99%
“…However, when LysoTracker probes accumulate intracellularly for prolonged periods, the intracellular pH increases which may result in enhanced quenching of the fluorescent dye. Most commercially available lysosome probes require a short excitation wavelength, which considerably restricts the use of these probes in tissue imaging associated with low penetration depth, decreased solubility, and poor photostability due to wavelength restrictions17181920212223242526272829303132. To address this problem, Belfield et al recently developed a novel, two-photon absorbing fluorescence derivatives exhibiting selectivity for the lysosomes of HCT 116 colon cancer cells26.…”
mentioning
confidence: 99%